The importance of corporate political responsibility engaging on political party policy requires courage when it goes against industry dogma - Winston, Andrew S.; Doty, Elizabeth; Lyon, Tom (MIT Sloan Management Review, 2022)
It's disingenuous for companies to pretend they are passive observers of regulations, laws, or the political climate. Corporate political responsibility is a new variation of corporate social responsibility, describing the ideal ways in which businesses should engage with the key systems of society. It requires companies to manage conflicting views about when and how to use their voices and their political influence.
Keywords: Corporations -- Political activity; Social responsibility of business; Business ethics; Sociétés; Activité politique; Entreprises; Responsabilité sociale; Morale des affaires; Corporations; Political activity